The Role of Social and Emotional Adjustment in Mediating the Relationship Between Early Experiences and Different Language Outcomes - Law, James; Tamayo, Nathalie; Mckean, Cristina; Rush, Robert (Frontiers in Psychiatry, 2021)
Background: Studies have highlighted the relationship between early childhood experiences and later language and communication skills on the one hand and social and emotional adjustment on the other. Less is known about this relationship between different types of early experiences and their relationship to different communication skills over time. Equally important is the extent to which the child's behaviour is related to later outcomes affecting the relationship between the child's environment and aspects of their communication development. Method: Drawing on data from 5,000 children in Growing Up in Scotland, a representative sample of children born in 2003. This paper looks are the differential relationships between home learning environment (HLE) (reads books/storeys, engages in painting or drawing, reads nursery rhymes and teaches letter/shapes and parental mental health (PMH) (Depression, Anxiety and Stress Scale (DASS) in the first year of life and both structural language skills (“Listening Comprehension” and “Expressive Vocabulary” subtests of The Wechsler Individual Achievement Tests) and pragmatic competence (The Children's Communication Checklist) at 11 years and explores the extent to which they are mediated by social and emotional adjustment at school entry. Results: PMH was associated with pragmatics but not listening comprehension or vocabulary. By contrast HLE was associated with all three measures of communication. In the final mediated model social and emotional adjustment mediated the relationship between PMH and all three measures of communication. The mediation was statistically significant for the relationship between HLE and both pragmatics and listening comprehension but not for expressive vocabulary. The results are discussed in terms of the relationships concerned and what they tell us about the potential for targeted early interventions. Conclusions: The mediating role of socio-emotional adjustment at school entry points to the need for careful monitoring of children's social and emotional development in primary and middle childhood. Services and policy aimed at improving child outcomes through improving home learning environments must work hand in hand with those responsible for offering support for the mental health, social-emotional adjustment and wellbeing of parents and children from birth and into the school years.